IMPLEMENTATION OF THE PROJECT TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS THROUGHTHE ASSISTANCE OF PEER TUTOR TEACHERS AT SMP NEGERI 1 SAMPIT - MASPA S PULUHULAWA (STKIP MUHAMMADIYAH SAMPIT, 2022)
This study aims to determine the learning planning process of the Pancasila Student Profile Strengthening Project at SMP Negeri 1 Sampit based on peer tutors; and to find out the results of its implementation in terms of the activities of teachers and students. This research uses a School Action Research approach which is carried out in two cycles and uses qualitative descriptive methods. The results of this study are: First, the learning planning process of the project to strengthen the profile of Pancasila students at SMP Negeri 1 Sampit based on peer tutors begins with the identification of problems, readiness, planning, implementation, and evaluation of P5 learning. Second, the implementation of the learning project to strengthen the profile of Pancasila students at SMP Negeri 1 Sampit in terms of teacher and student activities shows that the results of the assessment of indicators of four teacher competencies have achieved the creteria of achievement. Pedagogic competence is at 75% - 80%, personality competence at 76% - 81%, social competence at 77% - 83% and professional competence at 83% - 87%. Meanwhile, the level of student activity in the P5 learning process is included in the good category where 95% of students can interact between students, 88% carry out literacy in the context of problem solving and as many as 92% of students are actively monitored in learning activities.Keywords: